Exploring Education Interventions for Stroke Prevention Among Adults and Older Individuals: A Scoping Review - Mehdi Abbasian; Hosna Rashidi Birgani; Roghayeh Khabiri; Leila Namvar; Leila Jahangiry (Health Science Reports)
ABSTRACT Background and Aims This investigation aims to conduct a comprehensive review of educational interventions targeting stroke prevention to provide effective preventive measures and optimize resource utilization in adults and the elderly populations. Methods A comprehensive literature search was conducted on PubMed, SCOPUS, and Embase for articles published online or in print until February 22, 2022. Inclusion criteria for studies were limited to the studies that examined stroke education or training interventions aimed at improving knowledge among adults aged 30 years and above, with a particular focus on older adults. Results A review of 97,848 papers was conducted, resulting in the inclusion of 19 papers. Of these, six were randomized controlled trials (RCTs), six were non‐randomized studies, five were campaign studies, one was a cross‐sectional study, one was a pilot study, and one was a prospective study. The provided information describes various interventions and educational programs related to stroke awareness, prevention, and management. The intervention subjects were categorized as awareness of warning signs and symptoms of stroke (n = 14), comprehensive awareness campaigns (n = 5), multilevel strategies for stroke education (n = 4), community‐based nursing education and rehabilitation program (n = 5), multimedia campaign for 9‐1‐1 awareness (n = 3), and self‐management interventions (n = 1). Conclusion The categorized interventions, addressing awareness of warning signs and symptoms, comprehensive awareness campaigns, multilevel strategies, community‐based nursing education and rehabilitation programs, multimedia campaigns for 9‐1‐1 awareness, and self‐management interventions, collectively enrich our understanding of the multifaceted approaches to stroke education.